PROTOCOL: Conflict of interest issues when engaging stakeholders in health and healthcare guideline development: a systematic review. Issue 2 (16th April 2022) - Khabsa, Joanne; Petkovic, Jennifer; Riddle, Alison; Lytvyn, Lyubov; Magwood, Olivia; Atwere, Pearl; Campbell, Pauline; Katikireddi, Srinivasa V.; Merner, Bronwen; Nasser, Mona; Chang, Stephanie; Jaramillo Garcia, Alejandra; et al.
Abstract: This is the protocol for a Campbell systematic review. The overall objective of this study is to gather and summarize the existing literature on conflict of interest issues when engaging stakeholders in guideline development.